A case of Fibrodysplasia Ossificans Progressiva associated with a novel variant of the ACVR1 gene - Serena Cappato; Rasa Traberg; Jolita Gintautiene; Federico Zara; Renata Bocciardi (Molecular Genetics & Genomic Medicine, 2021)
Abstract Background Fibrodysplasia Ossificans Progressiva (FOP) is a rare autosomal dominant disease characterized by congenital malformation of the great toes and progressive heterotopic ossification of soft tissues leading to cumulative disability. The genetic cause of FOP are mutations in the ACVR1 gene that encodes a type I receptor of Bone Morphogenetic Proteins. The most recurrent mutation in FOP patients is R206H affecting the Glycine‐Serine rich domain and causing the hyper‐activation of the receptor and the responsivity to the non‐canonical ligand, Activin A. In the present study, we described a 3‐years old child with early and highly suggestive clinical features of FOP who was found negative for the recurrent p.R206H substitution. Methods Molecular screening of the whole ACVR1 coding sequence and functional characterization in transfection‐based assays. Results and Conclusions We identified a novel, de novo variant in the fifth ACVR1 coding exon (NM_001111067.4:c.772A>T; NP_001104537.1:p.(R258W)). This substitution, never reported in association with FOP, affects a conserved arginine residue in the kinase domain of the protein. In silico analysis predicted the pathogenicity of this substitution, demonstrated by in vitro assays showing that the p.R258W ACVR1 mutated receptor acquires the ability to transduce the aberrant Activin A‐mediated signaling, as observed for the gene variants associated with FOP.